STRENGTHENING MORAL EDUCATION TO REDUCE BULLYING AMONG STUDENS - Djaelani, M. Anwar; Khozin, Khozin; Humaidi, M. Nurul Humaidi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research stems from deep concerns. That, every day the bad news continues to increase regarding bullying behavior which causes many victims among students. This research aims to analyze the causes of bullying among students and provide options for how to overcome it. The method used is a qualitative approach based on literature study. The analysis was carried out descriptively. From research, it was found that students tend to bully because their personalities are still unstable. The research concluded that there is a general tendency for the average student to imitate easily and therefore needs to strengthen morals or character. The results of the research can make a positive contribution to efforts to achieve one of the educational goals as stated in Law Number 20 of 2003 concerning the National Education System